2023
DOI: 10.1186/s13020-023-00749-1
|View full text |Cite
|
Sign up to set email alerts
|

Study on basic and clinical application of Shufeng Jiedu Capsule in treating respiratory tract infection

Abstract: Shufeng Jiedu Capsule (SFJDC), composed of eight herbs, is a big brand traditional Chinese medicine (TCM) for the treatment of different respiratory tract infectious diseases with good clinical efficacy and few side effects. It is clinically applied to acute upper respiratory tract infection(URI), influenza, acute exacerbation of chronic obstructive pulmonary disease (AECOPD), community-acquired pneumonia(CAP) and other diseases, due to its antibacterial, antiviral, anti-inflammatory, immunoregulatory and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In China, SFJD capsules are indicated for treating acute upper respiratory tract infections with symptoms such as fever, sore throat, headache, nasal congestion, runny nose, and cough ( Xia et al, 2018 ). In vitro and in vivo experiments have demonstrated that SFJD inhibits viral proliferation and attenuates inflammation associated with lung injury ( Han et al, 2023 ). Moreover, clinical trials have employed SFJD capsules for treating respiratory diseases characterized by symptoms such as fever or chills, sore throat, headache, nasal congestion, and cough ( Wang et al, 2020 ; Xia et al, 2020 ; Chen et al, 2021 ; Xia et al, 2021 ; Zhang et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%
“…In China, SFJD capsules are indicated for treating acute upper respiratory tract infections with symptoms such as fever, sore throat, headache, nasal congestion, runny nose, and cough ( Xia et al, 2018 ). In vitro and in vivo experiments have demonstrated that SFJD inhibits viral proliferation and attenuates inflammation associated with lung injury ( Han et al, 2023 ). Moreover, clinical trials have employed SFJD capsules for treating respiratory diseases characterized by symptoms such as fever or chills, sore throat, headache, nasal congestion, and cough ( Wang et al, 2020 ; Xia et al, 2020 ; Chen et al, 2021 ; Xia et al, 2021 ; Zhang et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%